Western experience in the area of priority of high-quality higher education - Keiss, Stanislavs; Grisins, Arkadijs (Business, Management and Economics Engineering, 2011)
The paper contains research results of contemporary foreign experience of the most developed countries on providing a strategic priority of high-quality higher education, including the growth of the role of continuity and creativity elements in it. The paper deals with the nowadays tendencies that are favourable to the increase of high-quality training of higher qualification specialists. These tendencies are based on a close integration of areas of higher education and science, and include the development of regional mechanisms of scientific and educational clusters, inherent to the majority of the most developed countries. There are also formulated some recommendations favouring the development of scientific and educational potential of Latvian higher education, finding itself in a situation of a deep crisis.